How the Supramolecular Nature of Lignohumate Affects Its Diffusion in Agarose Hydrogel - Klučáková, Martina; Kalina, Michal; Enev, Vojtěch (Molecules (Basel, Switzerland), 2020)
Lignohumate, as an industrially produced analog of natural humic substances, is studied from the point of view of its diffusion properties. This work focuses on its permeation ability, important in agricultural and horticultural applications, connected with its penetration into plant organs as leaves and roots. The hydrogel based on agarose was used as a model material for the diffusion of lignohumate. Two types of experiments were realized: the diffusion of lignohumate in the hydrogel diffusion couple and the diffusion of lignohumate from its solution into hydrogel. The diffusion coefficient of lignohumate in the hydrogel was determined and used for the modelling of the time development of concentration profiles. It was found that the model agrees with experimental data for short times but an accumulation of lignohumate in front of the interface between donor and acceptor hydrogels was observed after several days. The particle size distribution of lignohumate and changes in the E4/E6 ratio used as an indicator of molecular weight of humic substances were determined. The results showed that the supramolecular structure of lignohumate can react sensitively to actual changes in its environs and thus affect their mobility and permeability into different materials. A filtration effect at the interface can be observed as an accompanying phenomenon of the re-arrangement in the lignohumate secondary structure.
Keywords: diffusion; Macromolecular Substances; Algorithms; huminové látky; hydrogely; sefarosa; spreading; makromolekulární látky; supramolecular nature; Chemical Phenomena; hydrogel; Humic Substances; teoretické modely; lignohumate; algoritmy; Hydrogels; Sepharose; chemické jevy; Models, Theoretical